The Equations and Characteristics of the Magnetic Curves in the Sphere Space - Jianguo Sun (Advances in Mathematical Physics)
We investigate some geometrical properties of magnetic curves in S3 under the action of the Killing magnetic field V=a∂x+ b∂y+ c∂z. The other main result is provided about the classification of the equations of the geodesics in S3. Moreover, some most relevant graphs of the main results were drawn in this paper.